Analisis kepuasan pemustaka terhadap kualitas layanan website perpustakaan di masa pandemi COVID-19 - Anisa Sri Restanti; Munjiati Munjiati; Utik Nur Wijayanti; Uswatun Auliyani; Saefudin Saefudin (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction: Government policies in suppressing the spread of the COVID-19 pandemic creates a bigger challenge to provide better library services. Library websites become one important service in social distance. This study aims to find out the level of user satisfaction in the utilization of library websites during the COVID-19 pandemic. Data Collecttion Methods: The paper used a quantitative approach with surveys. Questionnaires are managed based on webqual variables. Data analysis: The survey data analysis used descriptive statistics with mean value. The mean value is based on the interpretation guidelines. Results and discussion: Library web statements showed the highest score while library web appearance showed the lowest. The average score of user satisfaction on the utilization of library websites is at a satisfactory level. The highest score is 28,04 on the information quality variable. The lowest score of 18,76 on the usability quality variable and interaction quality showed a score of 23,74. Conclusions: Based on the results of data analysis on the webqual variable, the level of user satisfaction in the utilization of library website during the COVID-19 pandemic is found in the satisfactory level.